Implementation of the Village Fund Utilization Policy in Stunting Prevention Efforts in Passo Village, West Kakas District, Minahasa Regency - Sumendap, Jeanne A.; Mokat, Jetty E. H.; Tumbel, Goinpeace H. (JR Education, 2025)
This study investigates the implementation of the Village Fund utilization policy in Passo Village, West Kakas District, Minahasa Regency, focusing specifically on its role in stunting prevention. Employing a qualitative descriptive approach, the research aims to evaluate how the policy is executed, identify supporting and inhibiting factors, and assess its impact on community health outcomes. The research draws on Van Meter and Van Horn's policy implementation model to interpret field findings. The results indicate that while participatory planning and accountable fund management have contributed positively to improved nutrition awareness and reduced stunting rates, significant barriers remain, including limited facilities, weak inter-agency coordination, and low community engagement. The study concludes that bridging the gap between policy planning and actual implementation is essential for sustainable impact.